Greetings and Farewells in Emails in Serbian Language - Лазић-Коњик, Ивана (Poznańskie Studia Slawistyczne, 2017)
In this paper we consider opening greetings and complementary closes (farewells) in emails written in Serbian language that make relatively independent communication entities with the most general purpose of initiating and concluding a correspondence as the form of phatic language function and in the same time with metalinguistic discourse function of indicating the beginning and the end. We examine their structure and lexical, semantic and pragmatic properties, and also stress the occurrence of new characteristics or tendencies in their use caused by this new medium of communication, i.e. email, as compared to traditional letter correspondence. Those are: higher degree of linguistic individualization, expression of creativity in communication, resorting to economy, linguistic reductions and omissions.